The genus Parnassia in Vietnam, and a checklist of Vietnamese Celastraceae - Pham, Ngoc Hoai; Ren, Ming-Xun; Nuraliev, Maxim S.; Trinh, Ngoc Bon; Nguyen, Tien Dat; Ragupathi, Gopi; Pham, van The (Phytotaxa, 2022)
We summarize the knowledge on taxonomy and distribution of the genus Parnassia in Vietnam. Two species of the genus are found in Vietnam. We report additional records of P. wightiana, which appears to inhabit the provinces Ha Giang and Yen Bai. We provide detailed morphological description of the Vietnamese populations of this species, and discuss their deviation from the known variation range of P. wightiana. We report for the first time the second species of Parnassia from Vietnam, and provisionally identify it as P. procul. Our discovery of this species in Lam Dong Province in southern Vietnam is the first record of the genus outside the northern highlands within the country. We illustrate both Vietnamese species of Parnassia with analytical photographs, and show their distribution on a map. Additionally, we present an updated checklist of the family Celastraceae in Vietnam, which reflects the most recent views on taxonomic boundaries of the family and its genera, and includes discoveries of the last years as well as some earlier reports absent in the previous works. In total, 17 genera and 93 species are accepted in the checklist.